2017
DOI: 10.1186/s12891-017-1411-x
|View full text |Cite
|
Sign up to set email alerts
|

Identifying subgroups of patients using latent class analysis: should we use a single-stage or a two-stage approach? A methodological study using a cohort of patients with low back pain

Abstract: BackgroundHeterogeneity in patients with low back pain (LBP) is well recognised and different approaches to subgrouping have been proposed. Latent Class Analysis (LCA) is a statistical technique that is increasingly being used to identify subgroups based on patient characteristics. However, as LBP is a complex multi-domain condition, the optimal approach when using LCA is unknown. Therefore, this paper describes the exploration of two approaches to LCA that may help improve the identification of clinically rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
41
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 18 publications
(42 citation statements)
references
References 48 publications
1
41
0
Order By: Relevance
“…It has thus been argued that research should advance towards clustering of patients who share similar features and prognostic factors across the biopsychosocial domains, and tune management to the characteristics of the different clusters (Hill et al, ). Studies using cluster analyses in the MSK patient population have either been confined to specific pain diagnosis (Barons et al, ; Carlesso, Raja Rampersaud, & Davis, ; de Luca, Parkinson, Downie, Blyth, & Byles, ; Murphy, Lyden, Phillips, Clauw, & Williams, ; Nielsen, Kent, Hestbaek, Vach, & Kongsted, ; Rabey, Smith, Beales, Slater, & O'Sullivan, ; Reme et al, ; Stynes, Konstantinou, Ogollah, Hay, & Dunn, ), a single subgrouping variable (i.e. pain sites; Hartvigsen, Davidsen, Hestbaek, Sogaard, & Roos, ; Lacey et al, ) or factors related to one specific dimension (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…It has thus been argued that research should advance towards clustering of patients who share similar features and prognostic factors across the biopsychosocial domains, and tune management to the characteristics of the different clusters (Hill et al, ). Studies using cluster analyses in the MSK patient population have either been confined to specific pain diagnosis (Barons et al, ; Carlesso, Raja Rampersaud, & Davis, ; de Luca, Parkinson, Downie, Blyth, & Byles, ; Murphy, Lyden, Phillips, Clauw, & Williams, ; Nielsen, Kent, Hestbaek, Vach, & Kongsted, ; Rabey, Smith, Beales, Slater, & O'Sullivan, ; Reme et al, ; Stynes, Konstantinou, Ogollah, Hay, & Dunn, ), a single subgrouping variable (i.e. pain sites; Hartvigsen, Davidsen, Hestbaek, Sogaard, & Roos, ; Lacey et al, ) or factors related to one specific dimension (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…The main focus in this study was the subgroup membership in the two subgroupings previously identified by way of two separately conducted LCAs [ 30 ], one using a traditional single stage approach and another using a two-stage approach [ 33 , 34 ]. No imputations were performed during the subgrouping analyses, as LCA uses a likelihood approach which accommodates the inclusion of patients with missing values.…”
Section: Methodsmentioning
confidence: 99%
“…This resulted in seven single-stage subgroups and nine two-stage subgroups. The selection of the preferred subgroup solutions for each LCA approach had been informed by both statistical performance measures and a qualitative evaluation of clinical interpretability (face validity) [ 30 ]. The qualitative evaluation emphasised differences between the subgroups that were not only on a continuum of severity, but distinct differences in scoring patterns across the baseline characteristic.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations